An experimental investigation of flame height and air entrainment rate of double jet fires. Issue 1 (2nd January 2018) - Wang, Kai; Tao, Changfa; Liu, Qin; Qian, Yejian; He, Peixiang
ABSTRACT: This paper presents an experimental investigation on the mean flame height and the air entrainment rate of double buoyancy-controlled jet fires. Three rectangular nozzles of different aspect ratios with different geometric shapes under the same sectional area were used in this paper. For each experimental condition, two identical nozzles with the same heat release rate were considered, but the distance between two nozzles varied. Experimental results show that the mean flame height decreases sharply with the distance at first, and then changes slightly with the further increase of the distance. Meanwhile, the value of the ratio of air entrainment increases with the distance. A correlation between the dimensionless flame height and dimensionless heat release rate resulting in a general linear relation has been developed, and a developed model for the ratio of air entrainment and the distance has been achieved.